Limited P-glycoprotein mediated efflux for anti-epileptic drugs. - Crowe, Andrew; Teoh, Y. (informa UK Ltd, 2006)
A variety of anti-epileptic drugs (AEDs) were tested for their ability to be transported by P-glycoprotein (P-gp) through Caco-2 monolayers using bi-directional (apical (Ap) to basolateral (Bas), and Bas to Ap) studies. Transport rates were equivalent in both directions for vigabatrin, gabapentin, phenobarbitone, lamotrigine and carbamazepine, being 0.7 × 10− 6, 0.1 × 10− 6, 34 × 10− 6, 36 × 10− 6 and 55 × 10− 6 cm/s, respectively. Phenytoin displayed a 20% increase in Ap to Bas transport, while topiramate and ethosuximide each had greater transport in the uptake direction, with both drugs showing no efflux. None of the transport rates for these drugs were affected by P-gp inhibitors. However, the efflux rate for acetazolamide was 3-fold higher than its uptake and this was significantly reduced by P-gp inhibitors. Thus, only one anti-epileptic, acetazolamide, was shown to be weak P-gp substrate, suggesting that P-gp efflux may not be a factor in relation to the development of resistance of epilepsy therapy.